Organizing sports events: The promoters’ perspective - Brochado, A. (2022)
This study aims to develop a battery of items that assess the factors affecting sports events’ success from the promoters’ perspective and a measurement tool that identifies these stakeholders’ main priorities based on the importance-performance analysis (IPA) framework. Design/methodology/approach: The research was conducted using mixed methods. In the first qualitative step, sports event management’s main dimensions were identified based on the existing literature and a comprehensive battery of corresponding items were developed via content analysis of interviews with experts. The second quantitative step focused on Lisbon, the 2021 European City of Sport. Promoters of 21 different medium or large sports events (number = 41 respondents) were asked to fill out a survey ranking each dimension’s items by performance and room for improvement. The IPA’s results are presented both for the overall sample and by promoter type (i.e. events with or without sports facilities). Findings: The 46 items identified fall into the following three categories: sports infrastructure, city image and hospitality and event management (i.e. pre-event, event and post-event). Pre-event includes stakeholder management, organigram and responsibilities, business plan, marketing mix, risk assessment and sponsorship management. Sponsorship management stands out among the areas considered a priority by event promotors. Originality/value: This study adds to the literature by offering a comprehensive approach to assessing empirically all stages of the event management process.